Chronic kidney disease among children in Guatemala - Alejandro Cerón; Meredith P. Fort; Chris M. Morine; Randall Lou-Meda (Pan American Health Organization, 2014)
OBJECTIVE: To describe the distribution of pediatric chronic kidney disease (CKD) in Guatemala, estimate incidence and prevalence of pediatric end-stage renal disease (ESRD), and estimate time to progress to ESRD. METHODS: This study analyzed the registry of the only pediatric nephrology center in Guatemala, from 2004-2013. Incidence and prevalence were calculated for annual periods. Moran's index for spatial autocorrelation was used to determine significance of geographic distribution of incidence. Time to progress to ESRD and associated risk factors were calculated with multivariate Cox regression. RESULTS: Of 1 545 patients from birth to less than 20 years of age, 432 had chronic renal failure (CRF). Prevalence and incidence of ESRD were 4.9 and 4.6 per million age-related population, respectively. Incidence was higher for the Pacific coast and Guatemala City. The cause of CRF was undetermined in 43% of patients. Average time to progress to ESRD was 21.9 months; factors associated with progression were: older age, diagnosis of glomerulopathies, and advanced-stage CKD at consultation. CONCLUSIONS: Prevalence and incidence of ESRD in Guatemala are lower than in other countries. This may reflect poor access to diagnosis. Areas with higher incidence and large proportion of CKD of undetermined cause are compatible with other studies from the geographic subregion. Findings on progression to ESRD may reflect delayed referral.